O azul fluminense: o anil no Rio de Janeiro colonial, 1749-1818 - Pesavento, Fábio (2005)
In a general way, little is known about the parallel activities to those considered most important (sugar and mining, mainly) in the Brazilian colonial economy. Hence, this article, in a introductory way, intends to analyze an important article among Rio de Janeiro exports during the last half of 18th century and the beginning of the 19th century: the indigo. The mannerism of this economic active reside in fact of the short favourable performace (1779-1807). The results, either qualitative (primary fonts) or quantitative, suggest that the end of this activity in Rio de Janeiro occured, mainly, on one hand, due to falsification practices by indigo growers and, on the other hand, the diversification of cultures (the substitution of indigo for rice, bean, cassava).